ESTIMATING OF PROFIT FUNCTION OF VEGGETABLE CROPS IN ALQOSH REGION FOR THE PRODUCTION SEASON 2019 - Shaba, S. F.; Barbaz, D. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The research aims to study the profit functions of vegetable crops. Cross-sectional data was used based on a random sample that included 200 farmers in Alqosh region within Nineveh Province for the 2018-2019 agricultural season. The results showed that there are vegetable crops which need a large amount of labor as labor costs amounted to about 71% of the total costs per acre in tomato production. It was also found that total costs were higher in tomato crop cultivation at the dunum level compared to other vegetable crops. In addition, profit function shows that the price of the product has a significant effect on profit compared to the rest of the independent variables in the functions of vegetable crops, as the parameter of tomato crop price was about 51603.22 and it was significant and approved according to the T-test at the level of 1%. The determination coefficient was about 79% in the function estimated by the OLS method. Problem of heteroscedasticity according to White’s general test was significant, so the estimation was done by the robust regression method to avoid that problem. That led to a decrease of the determination coefficient to about 55%, While the determinant factor of the cucumber crop reached about 72%, to be reduced to about 56% after addressing the problem of variability instability. The research recommended that farmers should be encouraged to expand tomato cultivation instead of other vegetable crops.